-162=-5x-6(6x-14)

Simple and best practice solution for -162=-5x-6(6x-14) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -162=-5x-6(6x-14) equation:



-162=-5x-6(6x-14)
We move all terms to the left:
-162-(-5x-6(6x-14))=0
We calculate terms in parentheses: -(-5x-6(6x-14)), so:
-5x-6(6x-14)
We multiply parentheses
-5x-36x+84
We add all the numbers together, and all the variables
-41x+84
Back to the equation:
-(-41x+84)
We get rid of parentheses
41x-84-162=0
We add all the numbers together, and all the variables
41x-246=0
We move all terms containing x to the left, all other terms to the right
41x=246
x=246/41
x=6

See similar equations:

| 76=-4+8x | | -6-4v=7v+1 | | H=(2x+9)L=(5x-3)W=(3x+2)V=7106 | | 2x+(4+x)=2(x+4)+17 | | 2(x+4)-2x=17 | | j+-13=-33 | | 3z+12=9z-16 | | 2y+3(5y−7)=47 | | 2/5=30/n | | 4v=-7 | | 4x+4(-5x+7)=172 | | 32​ w=12 | | 7b+2=3b+30# | | 4x−2(x+9)=6 | | 3w+12=6w+17 | | 2-n=6-18 | | 5n=-105 | | 4y+8=2y-30 | | 6(x−1)+8=32 | | 3x+6=9x+47 | | 2/3x+2/3x9=8 | | −8=−2x+11​ | | -0.375c-11=13= | | 7x+2(5x-14)=-113 | | -6x+5=89 | | 20w=10 | | 12(x-3)-1=5(-x+8)+4 | | 5a+36=9 | | 5m+4=m8 | | 8x/3=x+20 | | 4b+3=2b=11 | | -201=3x-4(-5x-13) |

Equations solver categories